Application of the Internet of Things in Monitoring and Controlling Water Quality of Goldfish in Aquariums - Mahara, Sabda; Yunizar, Zara; Nunsina, Nunsina (Malikussaleh University, Aceh, Indonesia, 2025)
Caring for ornamental fish in aquariums often presents significant challenges, primarily when maintenance relies on manual methods. Owners may face difficulties when they are unavailable to feed the fish or clean the aquarium, potentially compromising the health and well-being of the ornamental fish. Consistent water quality monitoring is critical to maintaining a stable and healthy environment for these aquatic creatures. To address these issues, this study developed an Internet of Things (IoT)-based system to monitor water conditions in real-time via an internet connection. By leveraging IoT technology, the system allows owners to access real-time data and remotely control aquarium parameters through a user-friendly interface, providing convenience and improved management. The system monitors essential water parameters, including temperature and pH levels, to sustain the fish's health and ensure the aquarium ecosystem's stability. Testing was conducted over two days, with data recorded at fifteen-minute intervals each day, and the results demonstrated that the system effectively monitored these parameters with sufficient accuracy. The collected data is presented in an intuitive table interface, making it easy for users to analyze trends and respond promptly to any irregularities. Additionally, the system features automatic actuator controls that allow necessary adjustments without requiring constant user involvement, significantly simplifying aquarium maintenance. The accompanying monitoring website further enhances usability by enabling users to check and manage water quality anywhere and anytime, providing flexibility and control. These features collectively ensure a more effective, efficient, and sustainable approach to ornamental fish care, ultimately improving aquarium management and fish well-being.